Diversity and antibacterial activity of bacteria isolated from the coastal marine sponges Amphilectus fucorum and Eurypon major - Margassery, L.; Kennedy, J.; O'Gara, Fergal; Dobson, A.; Morrissey, J. (Blackwell Scientific Publishers, 2012)
Aims: To assess the diversity and antimicrobial activity of culturable bacteria associated with two temperate-water marine sponges, Amphilectus fucorum and Eurypon major. Methods and Results: Sponge samples were collected in August 2008 and bacteria were cultured on several different media. The 16S rRNA gene of representative strains was sequenced to allow classification. It was found that Proteobacteria were the dominant group of bacteria cultured from both sponges, but overall, the bacterial composition was diverse and distinct between the sponges. The most notable features were the significantly higher proportion of firmicutes in E. major and the low frequency of actinobacteria in both sponges. Four bacterial isolates were identified as potentially novel species and will be characterised in future studies. Approximately 400 cultured bacteria were screened for antimicrobial activity against a collection of indicator strains, with only eight strains, all Pseudovibrio spp., displaying any such activity. These strains were active against Escherichia coli and Bacillus subtilis but not Staphylococcus aureus or a selection of fungal strains. Conclusions: Diverse and distinct populations of culturable bacteria are present in the coastal sponges A. fucorum and E. major. Only a minority of isolates produce antibacterial metabolites in culture, but this activity is common in Pseudovibrio spp. Significance and Impact of the Study: This study illustrates the diversity of sponge-associated bacteria and the need to increase our knowledge about the function of these symbiotic bacteria. The data suggest that production of antibacterial metabolites is restricted to a subset of species, with the majority involved in other functions. The importance of Pseudovibrio as a reservoir of antibacterial metabolites is also highlighted.